Karakteristik Toxic Parenting Anak dalam Keluarga - Rianti; Ahmad Dahlan (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
This research is motivated by the parenting pattern of parents towards their children. Parenting patterns are habits that parents do to their children such as nurturing, guiding and leading their children in the family. However, this is not the case with toxic parenting. In this toxic parenting style, parents will treat their children badly, for example, controlling their children too much, yelling at children, verbally abusing them, blaming children, criticizing and being selfish with the aim of being for the good of their children. But in reality, this condition will make children depressed, depressed, stressed, and not confident. The purpose of the study was to determine the characteristics of toxic parenting of children in the family by using the literature study method with data collection techniques in the form of information from written sources. Based on the results of research on toxic parenting, it can be concluded that toxic parenting is very dangerous and has a large negative effect on the development of children in the future. This is because this kind of parenting has a link that the child will do when he grows up and has children, because he thinks that the parenting style carried out by his parents is good. To avoid toxic parenting, parents must try to recognize their child's behavior, provide opportunities for children, control emotions and establish good communication with children.